Taxonomic novelties in Myrosmodes (Orchidaceae) from the northwestern Argentine Andes - Monsalvo, Maria Alexandra; Sanchez, Marcela Ines; Fortunato, Renee Hersilia (Springere, 2021)
Myrosmodes noemiae (Orchidaceae), a new species from the Puna biome in the high northwestern Argentine Andes, is described and illustrated. This species is currently known from a single population; its habitat, a distribution map, and a key to distinguish it from other species of Myrosmodes growing in the Andean region are presented. In addition, we present an updated distribution of M. gymnandra, clarify the holotype of M. nubigena, and designate a lectotype for Altensteinia paludosa, the basionym of Myrosmodes paludosa.